Randall foils versus big blades: Comparative analysis in on-water sprint rowing - Cardoso, R.; Rios, M.; Cardoso, F.; Bouicher, S.; Abraldes, J. A.; Gomez, B. B.; Vilas-Boas, J. P.; Fernandes, R. J. (International Journal of Sports Physiology and Performance, 2025)
Purpose: We evaluated the technical and energetical impact of using Randall foils versus simple Big blades during a maximum rowing effort in field conditions.